Adaptación a las nuevas realidades: un desafío para las instituciones globales y regionales del comercio internacional - Peña, Félix (2011)
In this article, the author analyzes the different "stressful" situations that present themselves in the main areas of international cooperation. Such situations may have the potential to endanger the future of complex multinational structures such as the World Trade Organization, the European Union and MERCOSUR.